2004
DOI: 10.1359/jbmr.0301245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 6-Month Whole Body Vibration Training on Hip Density, Muscle Strength, and Postural Control in Postmenopausal Women: A Randomized Controlled Pilot Study

Abstract: High-frequency mechanical strain seems to stimulate bone strength in animals. In this randomized controlled trial, hip BMD was measured in postmenopausal women after a 24-week whole body vibration (WBV) training program. Vibration training significantly increased BMD of the hip. These findings suggest that WBV training might be useful in the prevention of osteoporosis.Introduction: High-frequency mechanical strain has been shown to stimulate bone strength in different animal models. However, the effects of vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
591
13
91

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 649 publications
(732 citation statements)
references
References 38 publications
37
591
13
91
Order By: Relevance
“…In healthy individuals, some positive effects are reported, for example increased muscle strength in untrained females, 4 improved balance, muscle strength or gait performance in the elderly 5,6 whereas other studies have found no or insufficient effects of WBV training. 7,8 In individuals with stroke or other neurological diseases, few studies have evaluated the effects of WBV training and the results differ also in those studies.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…In healthy individuals, some positive effects are reported, for example increased muscle strength in untrained females, 4 improved balance, muscle strength or gait performance in the elderly 5,6 whereas other studies have found no or insufficient effects of WBV training. 7,8 In individuals with stroke or other neurological diseases, few studies have evaluated the effects of WBV training and the results differ also in those studies.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…Several papers [18][19][20] have analysed bone mineral density response to physical exercise in older women, but the results are conflicting, depending of the anatomical measurement region. However, for our knowledge, few tried to establish some kind of relationship between the amount of training and modifications achieved in bone mass 9,13 .…”
Section: Discussionmentioning
confidence: 99%
“…In regard to body composition, fat and muscle masses remained constant, which implies stopping aging related changes (Gómez-Cabello, Rodríguez, Vila-Maldonado, Casajús, & Ara, 2012;Tabernero et al, 2001). However, several interventions evidence that reducing fat mass and increasing muscle mass in older people is possible (Villareal et al, 2011;Solverg et al, 2013).…”
Section: Discussionmentioning
confidence: 99%